Methylmalonic acid at the serum level in the elderly contributes to cell growth via mitochondrial dysfunction in colorectal cancer cell spheroids - Arowu R. Tanaka; Chiho Murakami; Hideya Yamamoto (Biochemistry and Biophysics Reports)
Methylmalonic acid (MMA) is a small molecule produced during the metabolism of propionate and branched-chain amino acids. Recently, it has been reported that the blood concentration of MMA increases with age and promotes lung cancer metastasis. However, little is known regarding its effects on cancers other than lung cancer. In the present study, we examined the effects of MMA on colorectal cancer cell spheroids. We found that MMA promoted the proliferation of colorectal cancer spheroids at physiological concentrations that can be exhibited by the elderly and induced mitochondrial reactive oxygen species generation, which in turn affected the promotion of cell growth. MMA treatment also induces a metabolic shift in the glycolytic system. These results suggest that MMA may promote cancer cell proliferation by decreasing mitochondrial function, inducing a metabolic shift, and provide new insights into the effects of aging on cancer.